The Effect Of Health Education With The Lovaas Method Booklet / Applied Behavior Analysis (ABA) To Parents' Knowledge In Training Autism Children At Sdlb Bojonegoro - Miadi, Miadi; Lutfiya, Alfi; Hidayat, Enung Mardiana; Ambarwati, Rini (Jurnal Riset Kesehatan, 2024)
Autism has a several disorder such as social interaction, communication, patterns play, activities and interests. How to help increase ability child autism through therapy. Lovaas method or Applied behavior analysis (ABA) is an intensive, structured, later teaching program capable transform A behavior and abilities complex become simple components for increase ability compliance and contact eyes in children. Collaboration between parents and parties school is needed in giving therapy. The aim of this study for analyze influence of educational media in the form of a booklet about Lovaas technique or Applied Behavior Analysis (ABA) towards enhancement parental knowledge in therapy child autism. Pre- experimental research design with a one group pretest-posttest design approach. Taking sample use total sampling method with a sample of parents who have child autism a total of 30 people. Instrument study about knowledge use questionnaire. Data analysis used the Wilcoxon test. Research result showing that there is change from mark pretest and posttest from parents who have child autism. The Wilcoxon test results show P Value of 0.000, there is influence educational media in the form of a booklet about Lovaas technique / applied behavior analysis (ABA) towards enhancement parental knowledge in therapy child autism at SDLB Putra Harapan Bojonegoro. Health education using booklet media is necessary given in a way sustainable to parents with children autism.